Low-shrinkage creep-resistant plastic wood product and preparation method thereof
By using raw materials with specific ratios to prepare plastic wood products, the problems of low impact strength and thermal deformation of existing plastic wood products at low temperatures are solved, and the effects of high creep resistance and low environmental impact are achieved.
Patent Information
- Application Number
- CN202411522920.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-14
AI Technical Summary
Existing plastic wood products have low impact strength at low temperatures, are easily affected by ambient temperature to cause thermal deformation, and the tensile creep modulus needs to be improved.
Use polypropylene, high-density polyethylene, eucalyptus/walnut shell/montmorillonite composite modified powder, end-hydroxyl polybutadiene@graphene/ZnO2/CaO, alkaline magnesium sulfate whiskers, γ-glycidyl ether oxygen Propyltrimethoxysilane and antioxidants are used to prepare plastic wood products with low shrinkage and creep resistance.
It improves the low-temperature impact strength and creep resistance of plastic wood products, reduces the linear thermal expansion coefficient, increases the thermal deformation temperature, and has a wide range of raw materials, low toxicity, and is easy to recycle and utilize, avoiding environmental pollution.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic-wood composite materials, and in particular to a low-shrinkage, creep-resistant plastic-wood product and a preparation method thereof. Background Art
[0002] The production process of wood-plastic composite materials generally includes blending, extrusion, molding, grinding, cutting, etc. of wood powder and plastic particles. It has the advantages of being recyclable, moisture-proof, anti-corrosive, and durable.
[0003] At present, plastic wood products are widely used. For example, Chinese invention patent CN113912965B discloses a plastic wood composite material photo frame and its preparation method, which contains: 100 parts of polyvinyl chloride plastic particles, 45 parts of wood powder, 24-30 parts of attapulgite clay with an average particle size of 30-50 μm, 1-1.2 parts of mesoporous molecular sieve, 5-8 parts of chlorinated polyethylene, 1-2 parts of foaming agent, 1.8-2 parts of lead salt heat stabilizer, 3.2-4 parts of metal soap heat stabilizer and 1.2 parts of epoxy plasticizer. The prepared plastic wood composite material photo frame has a frame strip with low density, low brittleness, high hardness, high strength and excellent impact resistance.
[0004] However, the lead salt stabilizers used in the raw materials are highly toxic and can easily produce sulfur pollution, causing environmental pollution problems. At the same time, since plastic wood materials are easily affected by ambient temperature and produce problems such as thermal deformation and low low-temperature impact strength, the tensile creep modulus of the existing technology needs further research and improvement.
[0005] Based on this, the present invention designs a low-shrinkage and creep-resistant plastic wood product and a preparation method thereof to solve the above problems. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a low-shrinkage and creep-resistant plastic wood product and a preparation method thereof.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] A low-shrinkage and creep-resistant plastic wood product is prepared from the following raw materials in parts by weight: 10 to 18 parts of polypropylene, 22 to 35 parts of high-density polyethylene, 58 to 83 parts of eucalyptus / walnut shell / montmorillonite composite modified powder, 10 to 15 parts of terminal hydroxyl polybutadiene@graphene / ZnO2 / CaO, 7 to 15 parts of basic magnesium sulfate whiskers, 3 to 4.6 parts of gamma-glycidyloxypropyltrimethoxysilane, and 0.3 to 1 part of an antioxidant.
[0009] Furthermore, the mass composition of the eucalyptus / walnut shell / montmorillonite composite modified powder is: 2-7 parts of eucalyptus, 11-14 parts of walnut shell, 6-10 parts of montmorillonite, and 2-4 parts of sodium silicate.
[0010] Furthermore, the preparation method of the eucalyptus / walnut shell / montmorillonite composite modified powder is:
[0011] A. Grind eucalyptus, walnut shell and montmorillonite into powder particles respectively, sieve eucalyptus particles through 200-300 mesh, walnut shell particles through 200-300 mesh, and montmorillonite particles through 100-200 mesh;
[0012] B. Prepare 22-25% sodium silicate solution with sodium silicate for standby use;
[0013] C. Eucalyptus particles, walnut shell particles and montmorillonite particles are evenly mixed and evenly sprayed with sodium silicate solution; they are placed under stirring conditions of 120-150 r / min, high temperature of 95-105°C, and medium pressure of 2.3-4.28 MPa for 1-2 hours to obtain eucalyptus / walnut shell / montmorillonite composite modified powder.
[0014] Furthermore, the mass composition of the hydroxy-terminated polybutadiene@graphene / ZnO2 / CaO is: 0.8-1.5 parts of graphene, 2-3.4 parts of ZnO2, 1.3-2.7 parts of CaO, and 1.6-2.2 parts of hydroxy-terminated polybutadiene.
[0015] Furthermore, the preparation method of terminal hydroxyl polybutadiene @ graphene / ZnO2 / CaO is as follows: graphene, ZnO2 and CaO are evenly mixed and calcined at 300-500°C for 3-5 hours, taken out and processed to nanoscale, and then the terminal hydroxyl polybutadiene is coated on its surface.
[0016] Furthermore, the following steps are included:
[0017] 1. Preparation of eucalyptus / walnut shell / montmorillonite composite modified powder:
[0018] A. Grind eucalyptus, walnut shell and montmorillonite into powder particles respectively, sieve eucalyptus particles through 200-300 mesh, walnut shell particles through 200-300 mesh, and montmorillonite particles through 100-200 mesh;
[0019] B. Prepare 22-25% sodium silicate solution with sodium silicate for standby use;
[0020] C. Eucalyptus particles, walnut shell particles and montmorillonite particles are evenly mixed and evenly sprayed with sodium silicate solution; the mixture is placed under stirring conditions of 120-150 r / min, high temperature of 95-105°C and medium pressure of 2.3-4.28 MPa for 1-2 hours to obtain eucalyptus / walnut shell / montmorillonite composite modified powder;
[0021] 2. Preparation of hydroxy-terminated polybutadiene@graphene / ZnO2 / CaO
[0022] Graphene, ZnO2 and CaO are mixed evenly and calcined at 300-500°C for 3-5h, taken out and processed to nanoscale, and then the surface is coated with terminal hydroxyl polybutadiene;
[0023] 3. Mix the hydroxy-terminated polybutadiene@graphene / ZnO2 / CaO and γ-glycidyloxypropyltrimethoxysilane and react at 105-113°C for 2.5-3.6h;
[0024] Fourth, the product obtained in step 3 is preliminarily mixed with polypropylene, high-density polyethylene, eucalyptus / walnut shell / montmorillonite composite modified powder, basic magnesium sulfate whisker and antioxidant, and then extruded into granules and extruded into shapes by an extruder to obtain a low-shrinkage and creep-resistant plastic wood product.
[0025] Furthermore, the initial mixing temperature is 168-175°C.
[0026] Furthermore, the extrusion granulation temperature range is 165-179°C; the extrusion molding temperature is 185-195°C.
[0027] Furthermore, the impact strength of plastic wood products is 6.96~7.27KJ / m 2 ; Tensile creep modulus is 18.8~21.6Mpa; Linear thermal expansion coefficient is 2.5~3.1*10 -5 / ℃; Heat deformation temperature: 163.2~178.5℃.
[0028] A low-shrinkage, creep-resistant plastic wood product prepared by the preparation method.
[0029] Beneficial Effects
[0030] The plastic wood product of the present invention has high low-temperature impact strength, good creep resistance, small linear thermal expansion coefficient, is conducive to inhibiting expansion and contraction, and has high thermal deformation temperature. Specifically, the impact strength of the plastic wood product is 6.96-7.27KJ / m 2 ; Tensile creep modulus is 18.8~21.6Mpa; Linear thermal expansion coefficient is 2.5~3.1*10 -5 / ℃; Heat deformation temperature: 163.2~178.5℃.
[0031] The plastic wood product of the present invention is prepared by using polypropylene, high-density polyethylene, eucalyptus / walnut shell / montmorillonite composite modified powder, terminal hydroxyl polybutadiene@graphene / ZnO2 / CaO, basic magnesium sulfate whisker, γ-glycidyloxypropyltrimethoxysilane and antioxidant. The raw materials are widely available and have low toxicity. The product is easy to recycle and avoids causing environmental pollution. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The present invention will be further described below in conjunction with the embodiments.
[0034] Example 1
[0035] This embodiment provides a method for preparing a low shrinkage and creep-resistant plastic wood product, comprising the following steps:
[0036] 1. Preparation of eucalyptus / walnut shell / montmorillonite composite modified powder:
[0037] A. Weigh 2 parts of eucalyptus, 14 parts of walnut shells, 10 parts of montmorillonite, and 4 parts of sodium silicate; grind the eucalyptus, walnut shells, and montmorillonite into powder particles respectively, sieve the eucalyptus particles through 200 mesh, the walnut shell particles through 300 mesh, and the montmorillonite particles through 100 mesh;
[0038] B. Prepare 22% sodium silicate solution with sodium silicate for standby use;
[0039] C. Eucalyptus particles, walnut shell particles and montmorillonite particles are evenly mixed and evenly sprayed with sodium silicate solution; the mixture is placed under stirring conditions of 120 r / min, high temperature of 105°C and medium pressure of 2.3 MPa for 2 hours to obtain eucalyptus / walnut shell / montmorillonite composite modified powder;
[0040] 2. Preparation of hydroxy-terminated polybutadiene@graphene / ZnO2 / CaO
[0041] Weigh 0.8 parts of graphene, 3.4 parts of ZnO2, 1.3 parts of CaO, and 2.2 parts of hydroxyl-terminated polybutadiene, mix the graphene, ZnO2, and CaO evenly, calcine at 300°C for 5 hours, take out and process to nanoscale, and then coat the surface of the graphene with hydroxyl-terminated polybutadiene;
[0042] 3. Mix 10 parts of hydroxy-terminated polybutadiene@graphene / ZnO2 / CaO and 4.6 parts of γ-glycidyloxypropyltrimethoxysilane, and react at 105°C for 3.6 hours;
[0043] 4. Preliminarily mix the product obtained in step 3 with 10 parts of polypropylene, 35 parts of high-density polyethylene, 58 parts of eucalyptus / walnut shell / montmorillonite composite modified powder, 15 parts of basic magnesium sulfate whiskers and 0.3 parts of antioxidant, and then extrude granulate and extrusion mold through an extruder to obtain a low-shrinkage and creep-resistant plastic wood product.
[0044] The initial mixing temperature is 168°C, the extrusion granulation temperature range is 165-170°C, and the extrusion molding temperature is 195°C.
[0045] Performance test results of plastic wood products:
[0046] Impact strength is 6.91KJ / m 2 . (GB / T 1843-2008, -50℃).
[0047] The tensile creep modulus is 18.8Mpa. (GB / T 11546.1-2008).
[0048] Linear thermal expansion coefficient 3.1*10 -5 / ℃(GB / T 24508-2020).
[0049] Heat deformation temperature: 178.5℃ (GB / T 1634.3-2004, 1.8MPa, 0.34mm).
[0050] Example 2
[0051] This embodiment provides a method for preparing a low shrinkage and creep-resistant plastic wood product, comprising the following steps:
[0052] 1. Preparation of eucalyptus / walnut shell / montmorillonite composite modified powder:
[0053] A. Weigh 7 parts of eucalyptus, 11 parts of walnut shells, 6 parts of montmorillonite, and 2 parts of sodium silicate; grind the eucalyptus, walnut shells, and montmorillonite into powder particles respectively, sieve the eucalyptus particles through 300 mesh, the walnut shell particles through 200 mesh, and the montmorillonite particles through 200 mesh;
[0054] B. Prepare 25% sodium silicate solution with sodium silicate for standby use;
[0055] C. Eucalyptus particles, walnut shell particles and montmorillonite particles are evenly mixed and evenly sprayed with sodium silicate solution; the mixture is placed under stirring conditions of 150r / min, high temperature of 95°C and medium pressure of 4.28Mpa for 1h to obtain eucalyptus / walnut shell / montmorillonite composite modified powder;
[0056] 2. Preparation of hydroxy-terminated polybutadiene@graphene / ZnO2 / CaO
[0057] Weigh 1.5 parts of graphene, 2 parts of ZnO2, 2.7 parts of CaO, and 1.6 parts of hydroxyl-terminated polybutadiene, mix the graphene, ZnO2, and CaO evenly, calcine at 500°C for 3 hours, take out and process to nanoscale, and then coat the surface of the graphene with hydroxyl-terminated polybutadiene;
[0058] 3. Mix 15 parts of hydroxy-terminated polybutadiene@graphene / ZnO2 / CaO and 3 parts of γ-glycidyloxypropyltrimethoxysilane, and react at 113°C for 2.5 hours;
[0059] 4. Preliminarily mix the product obtained in step 3 with 18 parts of polypropylene, 22 parts of high-density polyethylene, 83 parts of eucalyptus / walnut shell / montmorillonite composite modified powder, 7 parts of basic magnesium sulfate whiskers and 1 part of antioxidant, and then extrude granulate and extrusion mold through an extruder to obtain a low-shrinkage and creep-resistant plastic wood product.
[0060] The initial mixing temperature is 170°C, the extrusion granulation temperature range is 170-179°C, and the extrusion molding temperature is 185°C.
[0061] Performance test results of plastic wood products:
[0062] Impact strength is 7.27KJ / m 2 . (GB / T 1843-2008, -50℃).
[0063] The tensile creep modulus is 20.2Mpa. (GB / T 11546.1-2008).
[0064] Linear thermal expansion coefficient 2.8*10 -5 / ℃(GB / T 24508-2020).
[0065] Heat deformation temperature: 163.2℃ (GB / T 1634.3-2004, 1.8MPa, 0.34mm).
[0066] Example 3
[0067] This embodiment provides a method for preparing a low shrinkage and creep-resistant plastic wood product, comprising the following steps:
[0068] 1. Preparation of eucalyptus / walnut shell / montmorillonite composite modified powder:
[0069] A. Weigh 5.3 parts of eucalyptus, 12.6 parts of walnut shells, 8.3 parts of montmorillonite, and 2.8 parts of sodium silicate; grind the eucalyptus, walnut shells, and montmorillonite into powder particles, sieve the eucalyptus particles through 250 mesh, the walnut shell particles through 280 mesh, and the montmorillonite particles through 160 mesh;
[0070] B. Sodium silicate is prepared into a 23.6% sodium silicate solution for standby use;
[0071] C. Eucalyptus particles, walnut shell particles and montmorillonite particles are evenly mixed and evenly sprayed with sodium silicate solution; the mixture is placed under stirring conditions of 135 r / min, high temperature of 98°C and medium pressure of 3.68 MPa for 1.6 h to obtain eucalyptus / walnut shell / montmorillonite composite modified powder;
[0072] 2. Preparation of hydroxy-terminated polybutadiene@graphene / ZnO2 / CaO
[0073] Weigh 1.3 parts of graphene, 2.6 parts of ZnO2, 2.2 parts of CaO, and 1.8 parts of hydroxyl-terminated polybutadiene, mix the graphene, ZnO2, and CaO evenly, calcine at 400°C for 3.5 hours, take out and process to nanoscale, and then coat the surface of the graphene with hydroxyl-terminated polybutadiene;
[0074] 3. Mix 12.5 parts of hydroxy-terminated polybutadiene@graphene / ZnO2 / CaO and 3.8 parts of γ-glycidyloxypropyltrimethoxysilane, and react at 110°C for 3 hours;
[0075] 4. Preliminarily mix the product obtained in step 3 with 15.8 parts of polypropylene, 25 parts of high-density polyethylene, 68 parts of eucalyptus / walnut shell / montmorillonite composite modified powder, 10.5 parts of basic magnesium sulfate whiskers and 0.6 parts of antioxidant, and then extrude granulate and extrusion mold through an extruder to obtain a low-shrinkage and creep-resistant plastic wood product.
[0076] The initial mixing temperature is 175°C, the extrusion granulation temperature range is 176-179°C, and the extrusion molding temperature is 188°C.
[0077] Performance test results of plastic wood products:
[0078] Impact strength is 6.96KJ / m 2 . (GB / T 1843-2008, -50℃).
[0079] The tensile creep modulus is 21.6Mpa. (GB / T 11546.1-2008).
[0080] Linear thermal expansion coefficient 2.5*10 -5 / ℃(GB / T 24508-2020).
[0081] Heat deformation temperature: 167.6℃ (GB / T 1634.3-2004, 1.8MPa, 0.34mm).
[0082] Comparative Example 1
[0083] This embodiment provides a method for preparing a low shrinkage and creep-resistant plastic wood product, comprising the following steps:
[0084] 1. Preparation of eucalyptus / walnut shell / montmorillonite composite modified powder:
[0085] A. Weigh 5.3 parts of eucalyptus, 12.6 parts of walnut shells, 8.3 parts of montmorillonite, and 2.8 parts of sodium silicate; grind the eucalyptus, walnut shells, and montmorillonite into powder particles, sieve the eucalyptus particles through 250 mesh, the walnut shell particles through 280 mesh, and the montmorillonite particles through 160 mesh;
[0086] B. Sodium silicate is prepared into a 23.6% sodium silicate solution for standby use;
[0087] C. Eucalyptus particles, walnut shell particles and montmorillonite particles are evenly mixed and evenly sprayed with sodium silicate solution; the mixture is placed under stirring conditions of 135 r / min, high temperature of 98°C and medium pressure of 3.68 MPa for 1.6 h to obtain eucalyptus / walnut shell / montmorillonite composite modified powder;
[0088] 2. Weigh 1.3 parts of graphene, 2.6 parts of ZnO2, 2.2 parts of CaO, and 1.8 parts of hydroxyl-terminated polybutadiene, and mix them evenly to obtain a mixture A;
[0089] 3. Mix 12.5 parts of mixture A and 3.8 parts of γ-glycidyloxypropyltrimethoxysilane, and react at 110°C for 3 hours;
[0090] 4. Preliminarily mix the product obtained in step 3 with 15.8 parts of polypropylene, 25 parts of high-density polyethylene, 68 parts of eucalyptus / walnut shell / montmorillonite composite modified powder, 10.5 parts of basic magnesium sulfate whiskers and 0.6 parts of antioxidant, and then extrude granulate and extrusion mold through an extruder to obtain a low-shrinkage and creep-resistant plastic wood product.
[0091] The initial mixing temperature is 175°C, the extrusion granulation temperature range is 176-179°C, and the extrusion molding temperature is 188°C.
[0092] Performance test results of plastic wood products:
[0093] Impact strength is 5.01KJ / m 2 . (GB / T 1843-2008, -50℃).
[0094] The tensile creep modulus is 17.1Mpa. (GB / T 11546.1-2008).
[0095] Linear thermal expansion coefficient 4.1*10 -5 / ℃(GB / T 24508-2020).
[0096] Heat deformation temperature: 152.7℃ (GB / T 1634.3-2004, 1.8MPa, 0.34mm).
[0097] Comparative Example 2
[0098] This embodiment provides a method for preparing a low shrinkage and creep-resistant plastic wood product, comprising the following steps:
[0099] 1. Preparation of eucalyptus / walnut shell / montmorillonite composite modified powder:
[0100] A. Weigh 5.3 parts of eucalyptus, 12.6 parts of walnut shells, 8.3 parts of montmorillonite, and 2.8 parts of sodium silicate; grind the eucalyptus, walnut shells, and montmorillonite into powder particles, sieve the eucalyptus particles through 250 mesh, the walnut shell particles through 280 mesh, and the montmorillonite particles through 160 mesh;
[0101] B. Sodium silicate is prepared into a 23.6% sodium silicate solution for standby use;
[0102] C. Eucalyptus particles, walnut shell particles, montmorillonite particles and sodium silicate are uniformly mixed to obtain eucalyptus / walnut shell / montmorillonite composite modified powder;
[0103] 2. Preparation of hydroxy-terminated polybutadiene@graphene / ZnO2 / CaO
[0104] Weigh 1.3 parts of graphene, 2.6 parts of ZnO2, 2.2 parts of CaO, and 1.8 parts of hydroxyl-terminated polybutadiene, mix the graphene, ZnO2, and CaO evenly, calcine at 400°C for 3.5 hours, take out and process to nanoscale, and then coat the surface of the graphene with hydroxyl-terminated polybutadiene;
[0105] 3. Mix 12.5 parts of hydroxy-terminated polybutadiene@graphene / ZnO2 / CaO and 3.8 parts of γ-glycidyloxypropyltrimethoxysilane, and react at 110°C for 3 hours;
[0106] 4. Preliminarily mix the product obtained in step 3 with 15.8 parts of polypropylene, 25 parts of high-density polyethylene, 68 parts of eucalyptus / walnut shell / montmorillonite composite modified powder, 10.5 parts of basic magnesium sulfate whiskers and 0.6 parts of antioxidant, and then extrude granulate and extrusion mold through an extruder to obtain a low-shrinkage and creep-resistant plastic wood product.
[0107] The initial mixing temperature is 175°C, the extrusion granulation temperature range is 176-179°C, and the extrusion molding temperature is 188°C.
[0108] Performance test results of plastic wood products:
[0109] Impact strength is 6.24KJ / m 2 . (GB / T 1843-2008, -50℃).
[0110] The tensile creep modulus is 13.8Mpa. (GB / T 11546.1-2008).
[0111] Linear thermal expansion coefficient 3.4*10 -5 / ℃(GB / T 24508-2020).
[0112] Heat deformation temperature: 162.4℃ (GB / T 1634.3-2004, 1.8MPa, 0.34mm).
[0113] In summary, the plastic wood product of the present invention has high low-temperature impact strength, good creep resistance, small linear thermal expansion coefficient, which is conducive to inhibiting expansion and contraction, and high thermal deformation temperature. Specifically, the impact strength of the plastic wood product is 6.96-7.27KJ / m 2 ; Tensile creep modulus is 18.8~21.6Mpa; Linear thermal expansion coefficient is 2.5~3.1*10 -5 / ℃; Heat deformation temperature: 163.2~178.5℃.
[0114] The plastic wood product of the present invention is prepared by using polypropylene, high-density polyethylene, eucalyptus / walnut shell / montmorillonite composite modified powder, terminal hydroxyl polybutadiene@graphene / ZnO2 / CaO, basic magnesium sulfate whisker, γ-glycidyloxypropyltrimethoxysilane and antioxidant. The raw materials are widely available and have low toxicity. The product is easy to recycle and avoids causing environmental pollution.
[0115] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A low shrinkage and creep-resistant plastic wood product, characterized in that: The invention is prepared from the following raw materials in parts by weight: 10 to 18 parts of polypropylene, 22 to 35 parts of high-density polyethylene, 58 to 83 parts of eucalyptus / walnut shell / montmorillonite composite modified powder, 10 to 15 parts of terminal hydroxyl polybutadiene@graphene / ZnO2 / CaO, 7 to 15 parts of basic magnesium sulfate whisker, 3 to 4.6 parts of gamma-glycidyloxypropyltrimethoxysilane and 0.3 to 1 part of antioxidant.
2. The low shrinkage and creep resistant plastic wood product according to claim 1, characterized in that: in, The mass composition of the eucalyptus / walnut shell / montmorillonite composite modified powder is: 2-7 parts of eucalyptus, 11-14 parts of walnut shell, 6-10 parts of montmorillonite and 2-4 parts of sodium silicate.
3. The low shrinkage and creep resistant plastic wood product according to claim 2, characterized in that: The preparation method of eucalyptus / walnut shell / montmorillonite composite modified powder is as follows: A. Grind eucalyptus, walnut shell and montmorillonite into powder particles respectively, sieve eucalyptus particles through 200-300 mesh, walnut shell particles through 200-300 mesh, and montmorillonite particles through 100-200 mesh; B. Prepare 22-25% sodium silicate solution with sodium silicate for standby use; C. Eucalyptus particles, walnut shell particles and montmorillonite particles are evenly mixed and evenly sprayed with sodium silicate solution; they are placed under stirring conditions of 120-150 r / min, high temperature of 95-105°C, and medium pressure of 2.3-4.28 MPa for 1-2 hours to obtain eucalyptus / walnut shell / montmorillonite composite modified powder.
4. The low shrinkage and creep resistant plastic wood product according to claim 3, characterized in that: in, The mass composition of terminal hydroxyl polybutadiene@graphene / ZnO2 / CaO is: 0.8-1.5 parts of graphene, 2-3.4 parts of ZnO2, 1.3-2.7 parts of CaO, and 1.6-2.2 parts of terminal hydroxyl polybutadiene.
5. The low shrinkage and creep resistant plastic wood product according to claim 4, characterized in that: The preparation method of terminal hydroxyl polybutadiene@graphene / ZnO2 / CaO is as follows: graphene, ZnO2 and CaO are uniformly mixed and calcined at 300-500°C for 3-5 hours, taken out and processed to nanoscale, and then the terminal hydroxyl polybutadiene is coated on the surface thereof.
6. A method for preparing a low shrinkage and creep-resistant plastic wood product according to claim 5, characterized in that: The following steps are involved:
1. Preparation of eucalyptus / walnut shell / montmorillonite composite modified powder: A. Grind eucalyptus, walnut shell and montmorillonite into powder particles respectively, sieve eucalyptus particles through 200-300 mesh, walnut shell particles through 200-300 mesh, and montmorillonite particles through 100-200 mesh; B. Prepare 22-25% sodium silicate solution with sodium silicate for standby use; C. Eucalyptus particles, walnut shell particles and montmorillonite particles are evenly mixed and evenly sprayed with sodium silicate solution; the mixture is placed under stirring conditions of 120-150 r / min, high temperature of 95-105°C and medium pressure of 2.3-4.28 MPa for 1-2 hours to obtain eucalyptus / walnut shell / montmorillonite composite modified powder; 2. Preparation of hydroxy-terminated polybutadiene@graphene / ZnO2 / CaO Graphene, ZnO2 and CaO are mixed evenly and calcined at 300-500°C for 3-5h, taken out and processed to nanoscale, and then hydroxy-terminated polybutadiene is coated on the surface; 3. Mix the hydroxy-terminated polybutadiene@graphene / ZnO2 / CaO and γ-glycidyloxypropyltrimethoxysilane and react at 105-113°C for 2.5-3.6h; Fourth, the product obtained in step 3 is preliminarily mixed with polypropylene, high-density polyethylene, eucalyptus / walnut shell / montmorillonite composite modified powder, basic magnesium sulfate whisker and antioxidant, and then extruded into granules and extruded into shapes by an extruder to obtain a low-shrinkage and creep-resistant plastic wood product.
7. The method for preparing a low shrinkage and creep-resistant plastic wood product according to claim 6, characterized in that: The initial mixing temperature is 168-175°C.
8. The method for preparing low shrinkage and creep-resistant plastic wood products according to claim 6, characterized in that: The extrusion granulation temperature range is 165-179°C; the extrusion molding temperature is 185-195°C.
9. The method for preparing a low shrinkage and creep-resistant plastic wood product according to claim 6, characterized in that: The impact strength of plastic wood products is 6.96~7.27KJ / m 2 ; Tensile creep modulus is 18.8~21.6Mpa; Linear thermal expansion coefficient is 2.5~3.1*10 -5 / ℃; Heat deformation temperature: 163.2~178.5℃.
10. A low shrinkage and creep-resistant plastic wood product prepared according to the preparation method of claim 9.
Citation Information
Patent Citations
A wood-plastic composite photo frame and its preparation method
CN113912965B
Cited By
Toughening flame-retardant polypropylene composite material based on grading synergy and preparation method thereof
CN119912754A
PCR-PP bumper material with low linear expansion coefficient and preparation method thereof
CN121628248A